1973
DOI: 10.1029/wr009i006p01485
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of irrigating southern pines

Abstract: A climatic model developed for estimating the depressing effect of drought on the diameter growth of loblolly pines in the southern United States is used to project potential pine growth under conditions of no soil moisture deficit, which irriga.tion could assure. The regional distribution of the additional growth demonstrates that the benefits of irrigation would increase from the Atlantic coast. toward east Texas. The dollar value of the additional growth ba.sed on the current price of pulpwood is compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The 1200 mm per year of precipitation at our site was well distributed so that the lowest average monthly precipitation was 60 mm per month in May. The evaporative demand (vapor pressure deficit) may be relatively low due to fairly high humidity levels observed during the growing season (Manogaran, 1973). Lastly, Ewers et al (1999) found that fertilization improved water use efficiency-allowing growth to continue in the fertilized stands even though water availability may have been low.…”
Section: Discussionmentioning
confidence: 94%
“…The 1200 mm per year of precipitation at our site was well distributed so that the lowest average monthly precipitation was 60 mm per month in May. The evaporative demand (vapor pressure deficit) may be relatively low due to fairly high humidity levels observed during the growing season (Manogaran, 1973). Lastly, Ewers et al (1999) found that fertilization improved water use efficiency-allowing growth to continue in the fertilized stands even though water availability may have been low.…”
Section: Discussionmentioning
confidence: 94%
“…Pinus taeda is particularly sensitive to drought (Stransky and Wilson 1964). Thus, in the southeastern United States, soil moisture commonly limits the growth of P. taeda, one of the most widely naturally distributed and planted tree species (Coile 1936, Bassett 1964, Moehring and Ralston 1967, Manogaran 1973, Kramer 1983). However, based on the results from this study, water stress may develop in P. taeda even where soil moisture is high not far from the surface (Fig.…”
Section: Soil Moisture and Canopy Conductancementioning
confidence: 99%
“…The sensitivity of P. taeda to VPD, soil water content, and photosynthetically active radiation was verified by Ford et al (2004). The sensitivity to the first two factors was indicated by Manogaran (1973) and confirmed in Uruguay by Gándara et al (2014). For E. grandis hybrids, soil water content and atmospheric humidity was shown to be the most important growth modifiers in Brazil (Almeida et al 2007;Stape et al 2008Stape et al , 2010.…”
Section: Models Formulations and Use Of Growth Modifiersmentioning
confidence: 79%